Research on resource reconfiguration model of substrate carrier network based on hardware virtualization - HU Yu-xiang; LAN Ju-long; WU Jiang-xing (Tongxin xuebao)
Considering the heterogeneous environment of tri-network convergence,a resource reconfiguration model of substrate carrier network based on hardware virtualization was proposed.In terms of resource assigning algorithm which is the key issue in dynamic reconfiguration network,a resource assigning algorithm was proposed based on dynamic re-configuration at last.Based on the idea of platform support and component processing,the model facilitates the recon-figuration network based on hardware virtualization by supporting dynamic reconfiguration which could provide more flexible and high-speed multi-service networks.